Liquid crystals in the nineties and beyond - Kumar, Satyen (World Scientific, 1995)
This book is a collection of 13 articles, written by experts, on different aspects of the physics and applications of liquid crystals. In addition to giving self-contained review articles with good bibliography, the authors have discussed the anticipated or highly important and desirable breakthroughs in the near future in their respective fields. The book should provide readers with a good starting point, insight, and an indicator of what current important problems are. Good researchers should benefit in fine tuning their efforts to test the ideas put forward by the authors.